Impact of implementation of POSCO act on the status of Child Sexual abuse in India Legal Analysis - Ghanshyam Pathak; Dr. Shaukat Ali (International Journal of Medical Toxicology and Legal Medicine, 2024)
Worldwide, millions of children become child sexual abuse (CSA) victims every year; the problem is especially severe in several areas, including the Americas, Europe, and Africa. In 2012, India took a giant leap forward in combating this pressing issue with the passageway of the Protection of Children from Sexual Offences (POCSO) Act, which overcame both legal and social obstacles. This paper examines the ramifications of the POCSO Act and offers a thorough analysis of CSA in India, focusing on its legal impact. The article identifies three main obstacles to the POCSO Act’seffective implementation based on an analysis of field experience, media coverage, legal documents, and existing literature. These obstacles are underreporting of CSA cases, procedural complexity, and issues related to the presumption of guilt. These obstacles hinder the POCSO Act’s practical implementation, even though it is a critical step forward in protecting children and guaranteeing victim protection and justice. The report highlights the critical importance of addressing structural reforms and raising public awareness to effectively combat CSA in India.